THE EFFECT OF USING VIDEO TUTORIAL MEDIA ON STUDENTS’ WRITING SKILL IN WRITING PROCEDURE TEXT AT THE TENTH GRADE OF SMA KAMPUS NOMMENSEN PEMATANGSIANTAR - Eksaulina Simanjuntak; Indah Peronika Siahaan2; Imeliana Saragih; Diana Dian Sari Tampubolon; Dumaris Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Writing is an essential skill in English learning as it enables students to express ideas, thoughts, and feelings in a clear and meaningful way. However, many students still face difficulties in writing procedure texts, particularly in generating ideas, organizing steps, and using appropriate grammar and vocabulary. This study aims to examine the effectiveness of using video tutorial media on students’ writing skills in procedure text at the tenth grade of SMA Kampus Nommensen Pematangsiantar.This research employed a quantitative method with a pre-experimental design using one-group pre-test and post-test. The participants consisted of 23 students from class X-1 selected through purposive sampling. Data were collected using writing tests and analyzed through descriptive statistics and a paired sample t-test. The results showed that the students’ mean score increased from 56.5 in the pre-test to 76.9 in the posttest, indicating a significant improvement in their writing performance after being taught using video tutorial media.The findings suggest that video tutorial media is effective in improving students’ understanding of text structure, language features, and grammatical accuracy in writing procedure texts. In addition, the use of video tutorials enhanced students’ motivation and engagement during the learning process. Therefore, video tutorial media can be considered an effective and practical instructional tool to enhance students’ writing skills, particularly in learning procedure texts. Keyword : Writing Skill, Procedure Text, Video Tutorial Media, Students Writingng Achievement, English Language Teaching